Secondary structural features in the 70S RNAs of Moloney murine leukemia and Rous sarcoma viruses as observed by electron microscopy. - Murti, K G (1981)
The secondary structural features in the 70S RNAs of the Prague strain of avian Rous sarcoma virus, subgroup A (PR-RSV-A), and Moloney murine leukemia virus (M-MuLV) were compared by electron microscopy. The PR-RSV-A genome contained two subunits joined by a linkage structure as in the genomes of M-MuLV and other mammalian retroviruses. In both viral genomes, a highly reproducible hairpin occurred at about 70 nucleotides from the 5' end of each subunit and contained 320 +/- 8 nucleotides. The stable point of linkage between the subunits in both viral genomes involved fewer than 50 nucleotides and occurred at 466 +/- 9 nucleotides from the 5' end. This places the linkage about 350 nucleotides further toward the 3' end of the subunit than the binding site of primer tRNA. Another structural feature common to both genomes was a loop in each subunit. In M-MuLV, the loop contained 3.9 +/- 0.10 kilobases (kb) and occurred at a distance of 2.2 +/- 0.05 kb from the 5' end. In PR-RSV-A, the loop was smaller (2.3 +/- 0.10 kb) and further (3.3 +/- 0.10 kb) from the 5' end. When M-MuLV RNA was heated to 70, 85, or 90 degrees C and cooled, the hairpin consistently reformed at the 5' end. No other structures typical of the native molecules reappeared. In RNA samples heated to 70 degrees C, a new loop reproducibly occurred near the 5' end of each subunit, but this loop was not found in samples heated to higher temperatures. Based on all of these findings, we conclude that the genome of PR-RSV-A shares several features with M-MuLV and other mammalian retroviruses and that the primer tRNA molecules are not involved in the linkage of the two subunits in either genome. We also conclude that the dimer linkage and the loops in subunits are typical of the native molecules and that their formation requires a special environment.